Pengembangan Produk Buah Parijoto (Medinilla speciosa Blume) serta Potensinya sebagai Tanaman Obat : Review - Safrina, Devi; Susanti, Dian; Wijaya, Nur Rahmawati (Seminar Nasional Lahan Suboptimal, 2023)
Safrina, D., Susanti, D., & Wijaya, N.R. (2023). Product development of parijoto fruit (Medinilla speciosa Blume) and its potential as a medicinal plant : review. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 43–53).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Parijoto (Medinilla speciosa Blume; heterotypic synonym of Medinilla eximia (Jack) Blume) is a shrub from the Melastomataceae family which is known as an ornamental plant and is not widely known as a medicinal plant. Parijoto fruit contains tannins, flavonoids, glycosides, saponins, and alkaloids. People traditionally use parijoto fruit to treat canker sores, diarrhea, anti-inflammatory, antibacterial, anticancer, male fertility, and antioxidants. Several research results state that the parijoto plant has medicinal plant potential as an anti-obesity, anti-hyperlipidemia, anticancer, antibacterial, antioxidant, increasing fertility, hepatoprotector, and immunomodulator. Parijoto fruit has enormous potential as a medicinal plant, but it has yet to be widely developed by the community. This review article aimed to inform the public about the enormous opportunities in developing research from cultivation to product formulation. Based on the review results, information was obtained that the development of processed products is still minimal, and most of it is still on a research scale. Parijoto fruit has the potential to be developed into food products, including syrup, dodol, and jelly candy. Parijoto fruit can also be developed as a cosmetic preparation, such as body lotion and sunscreen cream. Apart from that, this plant also has the potential to be developed as a food coloring. Products made from parijoto fruit still need to be improved and have yet to be utilized by the wider community, so the potential for developing parijoto fruit is still enormous.